TIDAL GRAVITY OBSERVATIONS IN EASTERN SIBERIA AND ALONG THE ATLANTIC COAST OF FRANCE - Timofeev V.Yu.; Zapreeva E.A.; van Ruymbeke M.; Everaerts M.; Woppelmann G.; Gornov P.Yu.; Ducarme B. (My University, 2006)
Tidal gravity observations had been performed during more than 2 years (April 2001-September 2003) in Eastern Siberia with the LCR402. Simultaneously the gravimeter LCR1006 was recording in Chizé Observatory, not far from La Rochelle, in France. In France the station Chizé is the third of a network extending from "Aquitaine" (Ménesplet) to Brittany (Mordelles). All stations are located far enough from the sea to avoid very local effects in ocean tide loading. The main goal of the project was to compare the observed tidal parameters with the modelled ones, using different ocean models, i.e.: SCW80, CSR3, FES95, ORI96, CSR4, FES02, GOT00 and NAO99. A general conclusion is that the predictions using all the ocean tide models are in agreement within 0.2% for the area of Khabarovsk (Eastern Siberia). We may thus consider that a mean of all the oceanic models will have a precision better than 0.1%. It would thus be very difficult to improve the models using tidal gravity observations in this area. However, for the Atlantic coast of France the tidal parameters derived from different ocean tide models can disagree at the level of 3%. The observed results are close to the predictions derived from CSR3, CSR4 and FES02 models. © 2005 Elsevier Ltd. All rights reserved.
Keywords: OCEAN TIDES MODELS; TIDAL GRAVITY OBSERVATIONS; TIDAL LOADING